BERHAJI PADA MASA ORDE BARU DI SUMATERA BARAT 1966-1998 - KAKSIM S.PdI, M.Pd, KAKSIM (STKIP PGRI Sumatera Barat, 2011)
The implementation of hajj in Indonesia has different colors. The difference appeared inOrde Baru era, which in that time, government was implementing centralication system. Thesystem effecting the implementation of hajj in regions because all of decision depended on thecentral system. That thing made some problems into region those also held the hajj. The regiongovernment surely was slowed in acting because had to wait decesion from central government.This problem was effected in all regions in Indonesia including the Province of West Sumatera.West Sumatera Province is one of the region that has pilgrims every year in Orde Baru,beside had to held the hajj in order of central decision, West Sumatera Province also had tocooperate with region around such as North Sumatera Province. This is done in order todeparting the pilgrims to Mecca through Medan Embarcation, in case that West Sumatera hasno own any Embarcation yet. From the description, this written will view how theimplementation of hajj in West Sumatera in Orde Baru that was struggling for centralgovernment policy on the region interest.